La cuantificación del desarrollo histórico del capital en América del Sur - Rojas Cifuentes, Javiera (Ariadna Ediciones, 2023)
The book that we present below brings together the presentations (corrected and edited) of the first International Conference on Criticism of Political Economy, held during November 2021 in Chile. The exhibited works present, through a similar methodology, original estimates on the rate of profit and land rent in different South American countries. Although a unitary characterization of the region is not presented, by covering Argentina, Chile, Venezuela, Brazil, Uruguay and Paraguay, it constitutes a significant sample to expose the South American specificity. It thus allows progress in the elaboration of a coherent picture of the specific way in which the continent participates in the international division of labor under the appropriation of land rent by different social subjects, and its recovery by global social capital. Despite its partial nature, this book is a step in the knowledge of the way in which the interest of the entire working class is determined, an indispensable starting point for the development of any conscious political action.